Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.jseint.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperatively managed small- to medium-sized subscapularis tendon tears: magnetic resonance imaging evaluation with a minimum of 5 years of follow-up

Abstract: Background Isolated or combined subscapularis (SSC) tendon tears are frequently found in patients with shoulder pain. The purpose of this study was to evaluate the structural changes associated with SSC tear in a consecutive series of patients with nonoperatively treated small size to midsize SSC tendon tears using magnetic resonance imaging (MRI). Methods In this retrospective case series, all patients with an isolated or combined SSC tendon tear treated nonoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Although a good clinical outcome was obtained after arthroscopic repair of SSC tendon tears [ 15 17 ], the current sensitivity of MRI in SSC tendon tears was not ideal. The preoperative omission of SSC tendon tears could result in long-term pain and dysfunction of the shoulder, accompanied by progression of muscle atrophy, fatty infiltration, and increased tearing [ 18 ]. Yoon TH et al found that SSC tendon tears combined with advanced fatty infiltration had a high retear rate of 78.6% despite clinical improvement through surgery [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a good clinical outcome was obtained after arthroscopic repair of SSC tendon tears [ 15 17 ], the current sensitivity of MRI in SSC tendon tears was not ideal. The preoperative omission of SSC tendon tears could result in long-term pain and dysfunction of the shoulder, accompanied by progression of muscle atrophy, fatty infiltration, and increased tearing [ 18 ]. Yoon TH et al found that SSC tendon tears combined with advanced fatty infiltration had a high retear rate of 78.6% despite clinical improvement through surgery [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the repair of SSC tears with arthroscopy has achieved good clinical results, the sensitivity of diagnosis of SSC tears with MRI is not ideal at present 10 . If an SSC tear is missed, it may cause long-term shoulder pain or dysfunction with muscle atrophy, fat infiltration, and extended tear areas 11 . During arthroscopic rotator cuff repair, it was observed that SSC tears were missed in 43.1% of patients, and the fatty infiltration of SSC tendons, which was initially overlooked, showed further expansion during revision 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Intratendinous tear has not been introduced in the current classiications of SSC lesions [1][2][3]. Incomplete visualisation could lead to failure to diagnose SSC tears and subsequently have negative impacts on outcomes after rotator cuf repair [4][5][6].…”
Section: Introductionmentioning
confidence: 99%